Penerapan Metode Agile Development dalam Perancangan Sistem Informasi Pemesanan Tiket Travel Daring pada PT. Bahtera Atakana - Putri Mauliza; Riyadhul Fajri; Dedy Armiady (Jurnal Ilmu Komputer Aceh, 2026)
The advancement of information technology has encouraged transportation service companies to adopt digital-based operational systems. PT. Bahtera Atakana, an intercity travel service company operating in Bireuen, Aceh, still relies on a manual ticket booking system that is prone to recording errors, service delays, and limited access to customer information. This study aims to design and implement an online ticket booking information system using the Agile Development method, with the goal of producing a flexible, responsive system aligned with actual user needs. This research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. System development is carried out using the Agile Development method with an iterative approach through sprint planning, development, testing, and evaluation phases. The system is developed as a web-based application using PHP 8 with the CodeIgniter 3 framework, MySQL database, and supported by JavaScript and AJAX. The results show that the developed system effectively enables customers to search schedules, book tickets, process payments, and obtain e-tickets independently. The system reduces transaction time by up to 70% compared to the manual process. Black box testing ensures that all main functions operate according to user requirements. The implementation of the Agile Development method has proven effective in producing an adaptive, efficient, and user-centered information system.